DETERMINASI PRESTASI KERJA KARYAWAN TICKETING PT. KERETA API INDONESIA (PERSERO) DIVRE IV TANJUNG KARANG - Suliani, Tri (Jurnal Manajemen Magister Darmajaya, 2017)
This research aims to discover how big the influence of training variable, placement, motivation, job condition and job competence neither in partial or simultaneous test based on jobÂ  performance of ticketing officer in PT Kereta Api Indonesia, then to discover which is the dominant factor determined to ticketing officer of PT Kereta Api Indonesia. This research used quantitative desscriptive method. Population in this research contains 31 ticketing officer of PT Kereta Api Indonesia. Samples of this research are 30 people besides the writer. The data analysis technique used double linear regression, partial test and simultaneous test. The result of this research indicate that the training variable, placement, motivation, job condition and job competence do not influence significantly towards job performance neither in partial nor simultaneous test. Based on the existing variable shows that only job condition variable is the most dominant variable reach 0,344 or 34,4%.Keywords: Training, placement, motivation, job condition, job competence, work performance